Protein Kinase C Protocols - Newton, Alexandra C.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2003)
Protein kinase C impacts on nearly every aspect of signal transduction, placing it at the forefront of research in how cells transduce information. In Protein Kinase C Protocols, leading investigators from academia and industry present a comprehensive collection of classical and emerging laboratory techniques for the study of this influential protein, all optimized for successful and reproducible results. Described in step-by-step detail, these methods can be easily used to explore the structure, function, regulation, subcellular localization, and macromolecular interactions of protein kinase C. Included in this collection are easy-to-follow techniques to purify protein kinase C, to measure its activity and its membrane interaction in vivo and in vitro, and to identify substrates. There are also methodologies and techniques for measuring the phosphorylation state of protein kinase C, for expressing and analyzing the membrane-targeting domains of protein kinase C, and for detecting binding proteins. Additional chapters address pharmacological probes, genetic approaches, and protein kinase C in disease. Each protocol is introduced in the context of protein kinase C function and regulation and contains many notes on how best to deal with the problems that may occur. Comprehensive and authoritative, Protein Kinase C Protocols offers a timely compilation of biophysical, biochemical, cell biological, and molecular biological approaches that will ensure successful results in every laboratory working in this rapidly advancing field.
The Ins and Outs of Protein Kinase C -- Early Studies of Protein Kinase C -- Expression and Purification -- Expression and Purification of Protein Kinase C from Insect Cells -- Expression and Purification of Protein Kinase C? from Bacteria -- Measuring the Activity of Protein Kinase C -- Complexities in Protein Kinase C Activity Assays -- Enzyme Assays for Protein Kinase C Activity -- Subcellular Translocation of Protein Kinase C -- Measuring the Interaction of Protein Kinase C with Membranes -- Measuring the Interaction of Protein Kinase C with Membranes -- Fluorescence Imaging of Protein Kinase C Translocation in Living Cells -- Measuring the Binding of Protein Kinase C to Sucrose-Loaded Vesicles -- Use of Stopped-Flow Fluorescence Spectroscopy to Measure Rapid Membrane Binding by Protein Kinase C -- [3H]Phorbol 12,13-Dibutyrate Binding Assay for Protein Kinase C and Related Proteins -- Measuring the Phosphorylation of Protein Kinase C -- Protein Kinase C Phosphorylation -- Pulse-Chase Analysis of Protein Kinase C -- PDK-1 and Protein Kinase C Phosphorylation -- In Vitro Autophosphorylation of Protein Kinase C Isozymes -- Tyrosine Phosphorylation of Protein Kinase C -- Methods to Study Dephosphorylation of Protein Kinase C In Vivo -- Phosphopeptide-Specific Antibodies to Protein Kinase C -- Identifying Protein Kinase C Substrates -- Identifying Protein Kinase C Substrates -- A Chemical Genetic Approach for the Identification of Direct Substrates of Protein Kinases -- Studying the Optimal Peptide Substrate Motifs of Protein Kinase C Using Oriented Peptide Libraries -- Structural Analysis of Protein Kinase C -- Structural Analysis of Protein Kinase C -- Bacterial Expression and Purification of C1 and C2 Domains of Protein Kinase C Isoforms -- Crystallization of the Protein Kinase C? C1B Domain -- Methods for Detecting Binding Proteins -- Methods for Detecting Binding Proteins -- Detection of Protein Kinase-Binding Partners by the Yeast Two-Hybrid Analysis -- Glutathione S-Transferase Pull-Down Assay -- Overlay Method for Detecting Protein-Protein Interactions -- An Overlay Assay for Detecting Protein Kinase C-Binding Proteins and Substrates -- Functional Proteomic Analysis of the Protein Kinase C Signaling System -- Pharmacological Probes for Protein Kinase C -- Pharmacological Probes for Protein Kinase C -- Applications of Inhibitors for Protein Kinase C and Their Isoforms -- Phorbol Esters as Probes for the Study of Protein Kinase C Function -- Irreversible Inactivation of Protein Kinase C Isozymes by Thiol-Reactive Peptide Substrate Analogs -- Genetic Approaches to Studying Protein Kinase C -- Genetic Approaches to Studying Protein Kinase C -- Animal Models in the Study of Protein Kinase C Isozymes -- Genetic Manipulation of Protein Kinase C In Vivo -- Yeast as a Host to Screen for Modulators and Regulatory Regions of Mammalian Protein Kinase C Isoforms -- Protein Kinase C in Disease -- Protein Kinase C in Disease -- Characterization of the Role of Protein Kinase C Isozymes in Colon Carcinogenesis Using Transgenic Mouse Models -- Alcohol Addiction.
Keywords: Biochemistry; Biochemistry, general